1992
DOI: 10.1002/stem.5530100309
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy tested in a short‐term thymidine incorporation assay in primary cultures of ovarian adenocarcinomas

Abstract: Fifty-six tumor specimens from patients with ovarian adenocarcinoma were tested for sensitivity to single and combination drug regimens in a short-term antimetabolic assay measuring inhibition of thymidine incorporation. Response in primary cultures to drug combinations was compared with response to each component drug: cisplatinum, chlorambucil, adriamycin, etoposide and activated cyclophosphamide. Using cut-off criteria previously shown to correlate with "sensitive" and "resistant" tumors for single drugs, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Only a few such agents are known. Synergistic interactions have been reported for DDP with cytarabine (Andrews et al, 1988;Keane et al, 1990), 2'-deoxy-5-azacytidine (Frost et al, 1990), and alkylating agents (Frost et al, 1990;Lidor et al, 1991;Hayward et al, 1992). Anguidine (Hromas et al, 1984) and forskolin (Mann et al, 1991) have been noted to enhance the cellular uptake of DDP, whereas uptake is blocked by aldehydes (Dornish & Pettersen, 1985;Dornish et al, 1986) and ouabain (Andrews et al, 1988).…”
mentioning
confidence: 99%
“…Only a few such agents are known. Synergistic interactions have been reported for DDP with cytarabine (Andrews et al, 1988;Keane et al, 1990), 2'-deoxy-5-azacytidine (Frost et al, 1990), and alkylating agents (Frost et al, 1990;Lidor et al, 1991;Hayward et al, 1992). Anguidine (Hromas et al, 1984) and forskolin (Mann et al, 1991) have been noted to enhance the cellular uptake of DDP, whereas uptake is blocked by aldehydes (Dornish & Pettersen, 1985;Dornish et al, 1986) and ouabain (Andrews et al, 1988).…”
mentioning
confidence: 99%
“…Since, the primary treatment of EOC includes the combination chemotherapy using taxanes and platinum compounds, there seems to be a temptation to suggest performing in vitro EDR assay to drug combination. However, previous studies have demonstrated that combination drugs were not signiWcant better than a single drug in vitro EDR assay and it might be doubtful that testing EDR for drug combinations will signiWcantly improve the usefulness of the test (Sondak et al 1988;Hayward et al 1992;Piver et al 1998). Furthermore, the number of patients who showed EDR to both taxanes and platinum compounds was only 3, who were not useful for performing statistical analyses in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of published works on chemosensitivity testing in human ovarian cancer is not extensive, and results have been mixed [30,[44][45][46][47][48][49][50][51][52][53]. The clonogenic assay on ovarian carcinoma cells in culture was studied by Simmonds and McDonald [45] at the Royal Infirmary and Cell Laboratory of Glasgow in 1984.…”
Section: Atp Assaymentioning
confidence: 99%
“…Hayward et al [50] reported in 1992 from the Royal Melbourne and Royal Brisbane Hospitals in Australia on a study using the thymidine uptake assay in 16 human ovarian cancers where clinical follow-up results were available. Sensitivity was correctly predicted in nine of 11 cases and resistance in three of five cases for an overall correlation of 75%.…”
Section: Atp Assaymentioning
confidence: 99%